Analisis Cost-To-Serve Dan Customer Profitability Dengan Time-Driven Activity-Based Costing - Edwina Meilani Hartono (JAK (Jurnal Akuntansi) Kajian Ilmiah Akuntansi, 2021)
Cost-to-serve is the most important approach for customers, products, and how to manage them with the appropriate costs. Cost-to-serve targets aspects of efficiency, product mix, and rationalization in customer management. Many entities are only aware of the revenue generated by each customer and do not know how much it costs to establish relationships with customers. This study bridges this gap by identifying the use of cost-to-serve information and customer profitability analysis. The study was conducted with a case study method and a qualitative approach. Total cost-to-serve can be obtained by multiplying the cost driver rate and the level of actual activity usage for each customer. There are six customers who are not profitable or produce customer loss with four factories and two fellow distributors with an average of one transaction. Strategic decisions regarding choosing the right customer for PT X. are: (1) Applying price differentiation when the project is quiet because sales of PT X are seasonal and (2) Making cooperation with expeditions to maximize sales out of town because a strategy for serving out-of-town purchases is a profitable strategy.